Mechanical stimulation of the stigmas triggers switch from female to male phase in the protogynous trap flower of Aristolochia rotunda (Aristolochiaceae) - Blatrix, Rumsaïs; Kidyoo, Aroonrat; Matrougui, Inès; Samsungnoen, Paradorn; McKey, Doyle; Proffit, Magali (Mediterranean Botany, 2024)
Floral longevity is a selected trait that shows plasticity, allowing plants to balance resource allocation and reproduction. In dichogamous flowers—in which female and male functions are decoupled in time—the duration of the female phase is expected to vary according to pollination status. We used Aristolochia rotunda as a model to test the hypothesis that the female phase should be shortened following pollen deposition on the stigma, and to identify the signal for phase switching. Aristolochia flowers are protogynous (female phase first) and trap pollinators for several days (trap flowers). The four experimental treatments we applied to flowers, i.e. hand pollination, presence of pollinators with or without pollen load in the flower, and deposition of a nylon thread on the stigma, shortened the female phase to a similar extent, demonstrating that the duration of the female phase depended on the presence of pollinators, independently of whether or not they carried pollen, and that mechanical stimulation of the stigmas was the signal for phase switching. Temperature was also shown to shorten the female stage. This mechanism of post-anthesis floral changes is original because usually such changes are triggered by chemical interactions between pollen and stigmas. We interpret the mechanical signal used in A. rotunda for phase switching to be adaptive when pollinators are limiting, because switching to the male phase even if the trapped pollinator does not bring pollen would ensure fulfilling the flower’s male function.